Pembelajaran Penjumlahan dan Pengurangan Bilangan Dua Digit secara Simultan untuk Mengembangkan Intuisi Bilangan Siswa - Ratih Ayu Apsari; Sariyasa Sariyasa; I Gusti Putu Suharta; Baidowi Baidowi; Tabita Wahyu Triutami (Institut Agama Islam Negeri (IAIN) Tulungagung, 2021)
The learning of addition and subtraction that usually be done in sequence impact students’ tendency to separate type of the strategies employ to solve the related problems. In fact, there are a number of situations that can be observed and solved through both lenses. Therefore, in this study we designed a simultaneous addition and subtraction of two-digit numbers learning trajectory. The learning activities were constructed based on Realistic Mathematics Education (RME) Approach. This design study was conducted in three steps consist of preliminary study, teaching experiments, and retrospective analysis. The teaching experiments were done in two cycle, the first was done with four students and the second was done with 33 students in two classes of an elementary school located in Singaraja, Bali. The data related to number sense ability were gathered from observation and students’ written work in solving worksheet and post-test. The collected data were analyzed using constant comparative method. From the results, we found that a simultaneous learning of two-digit numbers addition and subtraction were effectively develop the students’ number sense and encourage the students to develop efficient counting strategies.